Evaluation of remote dielectric sensing (ReDS) technology-guided therapy for decreasing heart failure re-hospitalizations. (1st August 2017) - Amir, Offer; Ben-Gal, Tuvia; Weinstein, Jean Marc; Schliamser, Jorge; Burkhoff, Daniel; Abbo, Aharon; Abraham, William T
Abstract: Objective: We tested whether remote dielectric sensing (ReDS)-directed fluid management reduces readmissions in patients recently hospitalized for heart failure (HF). Background: Pulmonary congestion is the most common cause of worsening HF leading to hospitalization. Accurate remote monitoring of lung fluid volume may guide optimal treatment and prevent re-hospitalization. ReDS technology is a quantitative non-invasive method for measuring absolute lung fluid volume. Methods: Patients hospitalized for acute decompensated HF were enrolled during their index admission and followed at home for 90 days post-discharge. Daily ReDS readings were obtained using a wearable vest, and were used as a guide to optimizing HF therapy, with a goal of maintaining normal lung fluid content. Comparisons of the number of HF hospitalizations during ReDS-guided HF therapy were made, both to the 90 days prior to enrollment and to the 90 days following discontinuation of ReDS monitoring. Results: Fifty patients were enrolled, discharged, and followed at home for 76.9 ± 26.2 days. Patients were 73.8 ± 10.3 years old, 40% had LVEF above 40%, and 38% were women. Compared to the pre- and post-ReDS periods, there were 87% and 79% reductions in the rate of HF hospitalizations, respectively, during ReDS-guided HF therapy. The hazard ratio between the ReDS and the pre-ReDS period was 0.07 (95% CI [0.01–0.54] p  = 0.01), and between the ReDS and the post-ReDS period was 0.11 (95% CI [0.014–0.88] p  = 0.037). Conclusions: These findings suggest that ReDS-guided management has the potential to reduce HF readmissions in acute decompensated HF patients recently discharged from the hospital.